Transplantation of decellularised human amniotic membranes seeded with mesenchymal stem cell‐educated macrophages into animal models. Issue 7 (3rd February 2022) - Ebrahimi, Loghman; Samadikuchaksaraei, Ali; Joghataei, Mohammad Taghi; Safa, Majid; Abtahi Froushani, Seyyed Meysam; Ghasemian, Melina; Zolfaghari, Samira; Mozafari, Masoud; Brouki Milan, Peiman
Abstract: The reconstruction of chronic skin wounds remains a public health challenge in dermatology. Precisely controlling and monitoring the wound‐healing process should result in enhanced outcomes for the patient. Cell‐based therapies have shown great potential in medicine due to their immunomodulatory and healing properties. Herein, we produced activated macrophages by treating circulating monocytes with mesenchymal stem cell (MSC) supernatant. We also demonstrated the critical role of activated macrophages transplantation using amniotic membranes in accelerating wound healing in an animal wound model. The activated macrophages not only exhibited immunomodulatory cytokines like transforming growth factorβ (TGFβ) and interleukin 10 (and IL10) secretion but also showed attachment and proliferation ability on the amniotic membrane scaffold. Moreover, MSCs supernatant‐treated cells also displayed significant ARG1, CD206, and IL 10 genes expression. Inspired by the in vitro results, we examined the in vivo therapeutic efficacy of the activated macrophage transplantation using an acellular amniotic membrane carrier in a full‐thickness cutaneous wound model. The wound healing rate was significant in the group treated with macrophages generated via mesenchymal cell therapy seeded human amniotic membrane. There was less scarring in the wound sites after placing cell‐scaffold constructs in the wound sites in the animal models. Overall, macrophages stimulated with mesenchymal cells' supernatant exhibited improved healing processes in incisional wounds by decreasing the inflammatory phase, increasing angiogenesis, and reducing scar tissue development.